Impact of Financial Risks on the Performance of Cooperatives in Nepal - Kharel, Tika Ram; Panthi, Rishikesh (The Management Review, 2025)
The research aimed to assess the impact of financial risk on the performance of cooperatives in Nepal, focusing on credit, operational, and market risks are independent variables and financial performance is the dependent variable. The Research data was collected from financial statements and regulatory records spanning mid-July, 2015 to mid-July, 2024, though the dataset was unbalanced due to variations in the licensing years of the cooperatives. Descriptive statistics, including mean, standard deviation, and range, summarized the data, while correlation coefficient analysis examined the strength and direction of relationships between variables. Regression analysis explored the causal impact of financial risks on cooperative performance. The findings revealed that credit risk had a marginal but its positive effect on financial performance, operational risk had a significant and positive influence, and market risk demonstrated a substantial positive impact. The study underscores the importance of comprehensive risk management practices and recommends that cooperatives implement strategies addressing all dimensions of financial risk, including the recruitment of skilled risk management professionals, to enhance overall performance.